Bio-detheobromination of cocoa pod husks: Reduction of ochratoxin A content without change in nutrient profile - Oduro-Mensah, D.; Ocloo, A.; Lowor, S.T.; Mingle, C.; Okine, L.K.N.-A; Adamafio, N.A. (BioMed Central Ltd., 2018)
Background: Utilization of cocoa pod husks (CPH) in animal feed is hindered by the presence of theobromine, which is variably toxic to animals. Treatment of this agro-waste to remove theobromine, while preserving its nutrient content, would allow beneficial use of the millions of metric tonnes discarded annually. The aim of this study was to assess the suitability of selected theobromine-degrading filamentous fungi for use as bio-tools in degradation of theobromine in CPH. Results: The candidate fungi assessed in this study were an Aspergillus niger (AnTD) and three Talaromyces spp. (TmTD-1, TmTD-2, TvTD) isolates. All the fungi eliminated CPH theobromine, 0.15% w/w starting concentration, within 7days of start of treatment, and were capable of degrading caffeine and theophylline. The fungi decreased CPH ochratoxin A content by 31-74%. Pectin was not detectable in fungus-treated CPH whereas parameters assessed for proximate composition were not affected. Conclusions: The data provide ample evidence that the four isolates can be applied to CPH for the purpose of eliminating theobromine and decreasing ochratoxin A content without affecting nutrient profile. Comparatively, Talaromyces verruculosus TvTD was considered as most suitable for use as a bio-tool in detheobromination of CPH for animal feed. © 2018 The Author(s)
Keywords: Aspergillus; Cocoa pod husk; Ochratoxin A; Talaromyces; Theobromine